Letter to editor in response to: lepromatous leprosy in primigravida with early onset pre-eclampsia in third trimester: a rare case report - Gaikwad, Sudharani; Narang, Tarun; Dogra, Sunil; Kumar, Bhushan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
We read with great interest the case report on lepromatous leprosy in a primigravida with early-onset pre-eclampsia in the third trimester. The authors have brought attention to a rare and interesting clinical scenario. However, certain aspects of the case report need some clarifications